Improved Release of Monosaccharides and Ferulic Acid Using Enzyme Blends From Aspergillus Niger and Eupenicillium Parvum - Liu, Zhenghui; Shi, Enze; Ma, Feng; Zhou, Xin; Jiang, Kankan (Frontiers in Bioengineering and Biotechnology, 2022)
Supplementing commercial xylanase and cellulase with selected debranching enzymes only resulted in slight enhancement of the enzymatic hydrolysis of wheat bran autohydrolysis residues (WBAR) which was obtained at 160℃ over a 30-min period of autohdyrolysis, while a blend of enzymes from Aspergillus niger and Eupenicillium parvum achieved synergistic efficacy in this context. Using an equal mixture blend of these enzymes at a 0.5% (w/w) enzyme loading dosage with the addition of ferulic acid esterase (1 U/g substrate), the obtained hydrolysis yields were desirable, including 84.98% of glucose, 84.74% of xylose, 80.24% of arabinose, and 80.86% of ferulic acid. Following further separation using an HP-20 resin, the final ferulic acid recovery levels were as high as 62.5% of the esterified ferulic acid present within the initial WBAR input. Together, these data suggest that a combination of autohydrolysis and enzymatic hydrolysis using crude enzyme blends can efficiently achieve wheat bran enzymatic saccharification and associated ferulic acid release.